2000
DOI: 10.1111/j.1151-2916.2000.tb01709.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Catalyzed Synthesis of Organo‐Silica Nanoparticles

Abstract: A procedure has been developed which utilizes aminopropyltriethoxysilane (APS) as the catalyst and a comonomer in the production of hybrid organo-silica nanoparticles. Particles ranging from ca. 100 to 500 nm can be prepared using organo-silanes of the type RSi(OR) 3 , where R ‫؍‬ Me, vinyl, allyl, or other hydrophobic groups and R ‫؍‬ Me or Et, in a water/surfactant solution. Based on elemental analysis, up to 10 mol% of APS was incorporated into the siloxane particle network. It is thought that the amino gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 17 publications
4
44
0
Order By: Relevance
“…Positively charged amine groups of the APTMS suggest that MTMS in the oil phase diffuses to the oil-water interface where it reacts with the APTMS in the water phase to form a silica shell around the oil droplet. This effect was also observed by Ottenbrite [27] in their synthesis of organosilica nanoparticles, using aminopropyltriethoxysilane as the silica precursor. Jin found that increasing the volume of APTMS in water above 2% results in gelling, and no microcapsules were formed.…”
Section: Mtms-assisted Silica Coatingsupporting
confidence: 67%
See 1 more Smart Citation
“…Positively charged amine groups of the APTMS suggest that MTMS in the oil phase diffuses to the oil-water interface where it reacts with the APTMS in the water phase to form a silica shell around the oil droplet. This effect was also observed by Ottenbrite [27] in their synthesis of organosilica nanoparticles, using aminopropyltriethoxysilane as the silica precursor. Jin found that increasing the volume of APTMS in water above 2% results in gelling, and no microcapsules were formed.…”
Section: Mtms-assisted Silica Coatingsupporting
confidence: 67%
“…Adding MTMS or APTMS alone into water, there is no whitening or sol-gel reactions to be observed. Ottenbrite et al [27] reported similar sol-gel effect. Monodisperse spheres are about 900 nm in diameter.…”
Section: Mtms-assisted Silica Coatingmentioning
confidence: 77%
“…Exact amino group content at particle surface may provide additional stabilization through steric and charge repulsion to suppress the formation of aggomerates. 13 With increase of APS up to 75 mol %, large spheroidal particles and much agglomeration induced by strong interaction of hydrogen bond due to high amino molar fraction in the copolymer occur (as in Figure 1c). It is interesting that particle size initially decreases and then increases with the APS ratio.…”
Section: Resuits and Discussionmentioning
confidence: 96%
“…The first one takes into account the well-known ability of APTES to take part to the formation of spherical silica particles. 34b, 41,43,44 This process was suggested to occur via an aggregative pathway where primary particles fuse together to form larger objects. 44,45 By this mechanism, the final particles generally show a certain surface roughness, 44 but no specific porosity, 34b a fact that is actually confirmed by our own experiments on the SL-free materials.…”
Section: Sophorolipid/silica Interactionsmentioning
confidence: 99%